2011
DOI: 10.1111/j.1369-1600.2011.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking abstinence and depressive symptoms modulate the executive control system during emotional information processing

Abstract: Background Smoking abstinence disrupts affective and cognitive processes. In this study, functional magnetic resonance imaging (fMRI) was used to investigate the effects of smoking abstinence on emotional information processing (EIP). Methods Smokers (n=17) and nonsmokers (n=18) underwent fMRI while performing an emotional distractor oddball task in which rare targets were presented following negative and neutral task-irrelevant distractors. Smokers completed two sessions: once following 24-hr abstinence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…For example, nonsmokers with depressive symptoms have stronger neural responses to negative emotional information than those without DS (Felder et al, 2012). Among smokers, nicotine withdrawal promotes greater negative emotional interference on cognition (Froeliger et al, 2012; Gilbert et al, 2007)—the effects of which become worse with increasing levels of baseline depressive symptom severity (Froeliger et al, 2012; Gilbert et al, 2008). Furthermore, research on “depressive realism” suggests that persons with elevated DS engage in relatively more processing of negative information (Keller, Lipkus, & Rimer, 2002; Moore & Fresco, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, nonsmokers with depressive symptoms have stronger neural responses to negative emotional information than those without DS (Felder et al, 2012). Among smokers, nicotine withdrawal promotes greater negative emotional interference on cognition (Froeliger et al, 2012; Gilbert et al, 2007)—the effects of which become worse with increasing levels of baseline depressive symptom severity (Froeliger et al, 2012; Gilbert et al, 2008). Furthermore, research on “depressive realism” suggests that persons with elevated DS engage in relatively more processing of negative information (Keller, Lipkus, & Rimer, 2002; Moore & Fresco, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on the effectiveness of pictorial HWLs on cigarette packages has shown that cognitive and behavioral responses to HWLs predict cessation behavior (Borland et al, 2009; Fathelrahman et al, 2009; Yong et al, 2014). Depressive symptoms severity may lead to greater negative emotional interference on cognition (Froeliger, Modlin, Kozink, Wang, & McClernon, 2012), thus may influence the cognitive processing of negative emotional information that is displayed on cigarette pack HWLs. In addition, factors such as negativity bias that accompany depressive states (Moore & Fresco, 2012) may lead smokers with elevated DS to engage in more frequent or intensive processing of negative health related messages on HWLs.…”
Section: Depressive Disorders and Smokers’ Responses To Health Warninmentioning
confidence: 99%
“…For instance, several studies have demonstrated that brief abstinence from nicotine alters patterns of brain activation during the performance of effortful cognitive tasks (Froeliger, Modlin, Kozink, Wang, & McClernon, 2012;Kozink, Kollins, & McClernon, 2010;Kozink, Lutz, Rose, Froeliger, & McClernon, 2010;Sweet et al, 2010;Xu et al, 2005;Xu et al, 2006), and that these effects are moderated by age (Falcone et al, 2013), genotype (Loughead et al, 2009), and individual differences in performance (Nichols, Gates, Molenaar, & Wilson, 2013). More recently, fMRI has been used to characterize the mechanisms through which nicotine replacement therapy (Beaver et al, 2011;Cole et al, 2010) and other medications for the treatment of tobacco dependence (e.g., varenicline; Loughead et al, 2010) remediate withdrawal-related cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to drug-naïve controls, persons with substance-use disorders exhibit hypoactivation in frontal cognitive-control neural circuitry during conflict resolution tasks (Barrós-Loscertales, Bustamante et al 2011, Froeliger, Modlin et al 2013), and while processing salient emotional information (Sinha, Lacadie et al 2005, Goldstein, Alia-Klein et al 2009, Asensio, Romero et al 2010, Payer, Lieberman et al 2010, Augustus Diggs, Froeliger et al 2013, Froeliger, Modlin et al 2013). Moreover, acute withdrawal further exacerbates dysregulated prefrontal brain function across an array of neurocognitive tasks (Garavan, Kaufman et al 2008, Azizian, Nestor et al 2010, Kozink, Lutz et al 2010, Froeliger, Beckham et al 2012, Froeliger, Modlin et al 2012, Froeliger, Modlin et al 2012). …”
Section: Mechanisms Of Mindfulness and Addictionmentioning
confidence: 99%
“…In contrast, as compared to controls, substance abusers exhibit sustained hypofrontality in regions subserving cognitive control and error monitoring (Sinha, Lacadie et al 2005, Goldstein, Alia-Klein et al 2009, Asensio, Romero et al 2010, Payer, Lieberman et al 2010, Barrós-Loscertales, Bustamante et al 2011, Augustus Diggs, Froeliger et al 2013, Froeliger, Modlin et al 2013). Interestingly, among nicotine-dependent cigarette smokers, smoking abstinence as compared to satiety results in hyperfrontal response during neurocognitive tasks, without producing significant improvements in task performance or measured behavior (Kozink, Lutz et al 2010, Froeliger, Modlin et al 2012, Froeliger, Modlin et al 2012). Taken together, these findings, along with the broader literature (Goldstein and Volkow 2002), demonstrate that drug state-dependent sustained patterns of dysregulated top-down prefrontal neural function undergirds maladaptive behaviors found in substance-use disorders.…”
Section: Mechanisms Of Mindfulness and Addictionmentioning
confidence: 99%